Paeoniflorin Suppresses TBHP-Induced Oxidative Stress and Apoptosis in Human Umbilical Vein Endothelial Cells via the Nrf2/HO-1 Signaling Pathway and Improves Skin Flap Survival - Jiang, Jingtao; Dong, Chengji; Zhai, Liang; Lou, Junsheng; Jin, Jie; Cheng, Sheng; Chen, Zhuliu; Guo, Xiaoshan; Lin, Damu; Ding, Jian; Gao, Weiyang (Frontiers in Pharmacology, 2021)
Random-pattern skin flap is a vital technique frequently applied in reconstruction surgeries for its convenience and effectiveness in solving skin defects. However, ischemic necrosis, especially in the distal areas of the flap, still needs extra attention after surgery. Earlier evidence has suggested that paeoniflorin (PF) could stimulate angiogenesis and suppress ischemic cardiovascular disease. However, few studies have focused on the role of PF in flap survival. In this study, we have demonstrated that the human umbilical vein endothelial cells (HUVECs) treated with PF can alleviate tert-butyl hydroperoxide (TBHP)-stimulated cellular dysfunction and apoptosis. To better evaluate, HUVECs’ physiology, cell tube formation, migration, and adhesion were assessed. Mechanistically, PF protects HUVECs against apoptosis via stimulating the nuclear factor (erythroid-derived 2)-like 2 (Nrf2)/heme oxygenase 1 (HO-1) pathway. PF also downregulates mitochondrial ROS production to reduce excessive intracellular ROS production induced by TBHP and restore TBHP-induced mitochondrial depolarization. As a result, silencing Nrf2 partially abolishes the protective effect of PF exposure on HUVECs. In in vivo experiments, the oral administration of PF was shown to have enhanced the vascularization of regenerated tissues and promote flap survival. However, the PF-mediated protection was partially lost after co-treatment with ML385, a selective Nrf2 inhibitor, suggesting that PF is a crucial modulator regulating the Nrf2/HO-1 signaling pathway. In summary, our data have provided a new insight into PF as a potential therapy for enhancing random-pattern flap viability.